Literacy Learning Reading Writing in Elementary Schools - Saputra, Made Darma; Jampel, I Nyoman; Wibawa, I Made Citra (Universitas Pendidikan Ganesha, 2024)
Literacy learning in elementary schools has been implemented systematically, but there are still obstacles to student involvement and the effectiveness of strategies used by teachers. Some students have difficulty understanding, assessing, and reflecting on information from reading, while teachers need an innovative approach to improve students' literacy skills. This study aims to analyze the conditions of literacy learning and identify teachers' needs in implementing innovative literacy programs in elementary schools. A qualitative descriptive approach was used in this study, involving 91 grade III students and six teachers, using a saturated sampling technique. Data collection was carried out through observation, interviews, and distributing questionnaires to teachers and students, with instruments in the form of observation guidelines, interview guidelines, and structured questionnaires. The data obtained were analyzed using interactive analysis techniques that include data reduction, data presentation, and conclusion. The results of the study indicate that literacy learning has been going well but still requires strengthening in the variation of learning media and more effective strategies in increasing student involvement. The conclusion of this study confirms that efforts to strengthen literacy in elementary schools require more varied learning innovations based on student needs. The implications of this research provide insights for teachers and educational policymakers in designing more effective learning strategies to improve student's literacy skills sustainably.